Uncovering and quantifying the subduction zone sulfur cycle from the slab perspective - Ji-Lei Li (Nature Portfolio, 2020)
Sulfur is one of the key volatiles in Earth’s chemical cycles; however, sulfur speciation, isotopic composition, and flux during the subduction cycle remain unclear. Here, the authors provide direct constraints on subduction zone sulfur recycling from high-pressure rocks and explore implications for arc magmatism.